Hidden among the stars - Dobson, Melanie (Tyndale House Publishers, Inc., 2018)
The year is 1938, and as Hitler<U+2019>s troops sweep into Vienna, Austrian Max Dornbach promises to help his Jewish friends hide their most valuable possessions from the Nazis, smuggling them to his family<U+2019>s summer estate near the picturesque village of Hallstatt. He enlists the help of Annika Knopf, his childhood friend and the caretaker<U+2019>s daughter, who is eager to help the man she<U+2019>s loved her entire life. But when Max also brings Luzia Weiss, a young Jewish woman, to hide at the castle, it complicates Annika<U+2019>s feelings and puts their entire plan<U+2015>even their very lives<U+2015>in jeopardy. Especially when the Nazis come to scour the estate and find both Luzia and the treasure gone. Eighty years later, Callie Randall is mostly content with her quiet life, running a bookstore with her sister and reaching out into the world through her blog. Then she finds a cryptic list in an old edition of Bambi that connects her to Annika<U+2019>s story . . . and maybe to the long-buried story of a dear friend. As she digs into the past, Callie must risk venturing outside the safe world she<U+2019>s built for a chance at answers, adventure, and maybe even new love.